PELAYANAN KESEHATAN TERHADAP PASIEN PENGGUNA JAMKESDA DI RSUD BANGKINANG - Ainun, Fadhilah; Razif, Muhammad (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2015)
Hospital is society service that organize individual health service that prepare outpatient. Inpatient and ICU service. Jamkesda is social aid program to health service for poor society and incapable. Bangkinang „s RSUD is one of hospital that get referral from government yo give service to Jamkesda‟s member at Kampar regency.This research is doing at bangkinang‟s RSUD, Bangkinang city district,Kampar regency. The purpose of this research is done with using cualitative method, from result of deep interview and observation. As for the subject of this research is six people of Bangkinang‟s RSUD setvicers are administration, doctor and nurse. The technic of data collection uses purposive sampling.The summary that gotten from how the service and service problem at Bangkinang‟s RSUD to Jamkesda‟s members are very good. The cause of some problems caused hospital‟s party and Jamkesda‟s patient. Party of hospital who see Jamkesda‟s patient is from low economy will get simple service and caused Jamkesda‟s patient who not discipline. As for the solution that done for Bangkinang‟s RSUD hoped it can maintain and improve the quality of service for Jamkesda‟s members.Keyword: Service, Hospital, Jamkesda